A Comparative Study of Rhythmic Complexity Measures in Music Performance - Cihan Yaygın; Ozan Baysal; Yavuz Buruk; Barış Bozkurt (Konservatoryum)
The study of rhythmic complexity aims to determine the perceptual complexity of rhythms and how easily they can be remembered and performed. This research report evaluates two preliminary studies that approached rhythmic complexity from two complementary perspectives: conceptual understanding and performance. The research focuses on five rhythmic complexity measures: Lempel-Ziv, Keith, Tanguiane, Weighted Note-to-Beat Distance (WNBD), and Pressing. The rhythms used in the studies were created by the algorithmic software designed based on the conservatory entrance exam questions. In the first study, three expert raters evaluated the suitability and difficulty of 80 patterns. Their scores were compared with the values obtained from the complexity scales. The second study involved 11 conservatory students (5 female, 6 male) performing 16 selected rhythms from the initial pool. The results demonstrated varying degrees of alignment between different scales and expert predictions under different conditions. In fırst study, Pressing, WNBD, Keith and Tanguiane complexity scales were found to be consistent with expert raters. In the second study, the expert raters provided the most accurate predictions for rhythm repetition difficulty, followed by the WNBD scale and the Tanguiane scale. In addition, there was a significant negative correlation between the average time spent and performance scores.